2009
DOI: 10.1186/cc8115
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9, -10, and tissue inhibitor of matrix metalloproteinases-1 blood levels as biomarkers of severity and mortality in sepsis

Abstract: IntroductionMatrix metalloproteinases (MMPs) play a role in infectious diseases through extracellular matrix (ECM) degradation, which favors the migration of immune cells from the bloodstream to sites of inflammation. Although higher levels of MMP-9 and tissue inhibitor of matrix metalloproteinases-1 (TIMP-1) have been found in small series of patients with sepsis, MMP-10 levels have not been studied in this setting. The objective of this study was to determine the predictive value of MMP-9, MMP-10, and TIMP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 51 publications
13
115
2
1
Order By: Relevance
“…21 We found a significant increase of MMP-10 and CD40L in septic patients, particularly in the nonsurviving group. Thrombin, protein C pathway, activators and inhibitors of fibrinolysis, and PARs play vital roles in the crosstalk between inflammation and coagulation in sepsis, 28 but the role of CD40L in sepsis still remains unclear.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…21 We found a significant increase of MMP-10 and CD40L in septic patients, particularly in the nonsurviving group. Thrombin, protein C pathway, activators and inhibitors of fibrinolysis, and PARs play vital roles in the crosstalk between inflammation and coagulation in sepsis, 28 but the role of CD40L in sepsis still remains unclear.…”
Section: Discussionmentioning
confidence: 70%
“…This is associated with increased circulating levels of prothrombotic/inflammatory mediators, such as thrombin and CD40L, 4,7 and enhanced protease activity. 13,21 In this study, we describe for the first time that thrombin and CD40L act synergistically to induce MMP-10 both in vitro and in vivo, and to generate MPs carrying active MMP-10. The fact that thrombin mediates CD40 expression in ECs and that its inhibition significantly reduced MMP-10 expression strongly suggests that thrombin-induced CD40 upregulation could underlie this synergy.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that embedded soluble ion-releasing nanoparticles can affect proliferation and migration is not surprising as h-KC migration was previously shown to be affected by the release of iron and zinc ions as specified in the introduction [11], [12], [13], [14], [15], [16]. While KC differentiation, ex vivo, was already described to be induced by topical applications of zinc [16], this parameter has to be studied further in order to supplement the potential effects of our system on the KC behavior.…”
Section: Biological Testingmentioning
confidence: 99%
“…Hereby zinc was shown to take a part in the KC differentiation mechanisms [16]. Finally the scar tissues are remodelled by a turn over between degradation of type III collagen by MMPs and type I neocollagenesis, where respectively zinc and iron are imperative [11], [12], [13], [15]. Based on this, it may be concluded that an optimized ion release system for zinc and iron based on nanocomposites would be highly beneficial to aide in wound healing, while the embedded nanoparticles could serve as excellent ion release source because of their high surface-to-volume ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation